Human capital sustainability leadership: From personality traits to positive relational management - Di Fabio, Annamaria; Bonfiglio, Antonia; Palazzeschi, Letizia; Gori, Alessio; Svicher, Andrea (Frontiers in Psychology, 2023)
Constructing positive and supportive relationships is fundamental for healthy workers and healthy organizations and to cope with the current challenging work scenario. Organizations need to acknowledge the relevance of the relationships for workers and organizational well-being and adopt managing practices that enhance healthy relationships for sustainability and sustainable development. The current research sought to investigate the associations between Positive Relational Management (PRM) and Human Capital Sustainability Leadership (HCSL), taking into account personality traits. The Big Five Questionnaire (BFQ), the Positive Relational Management Scale (PRMS), and the Human Capital Sustainability Leadership Scale (HCSLS) were administered to 191 Italian workers. Findings displayed that PRM was able to add incremental variance over personality traits referring to HCSL. In terms of strength-based prevention perspectives for healthy organizations, Positive Relational Management may be a favorable construct linked to HCSL.